Unveiling Barriers: Challenges to Access High-Quality Education in South African Music Schools for Underprivileged and Marginalised Communities - Sakhiseni Joseph Yende (E-Journal of Humanities, Arts and Social Sciences)
South Africa’s music education landscape stands at the intersection of historical legacies, socio-economic disparities, and cultural intricacies, posing formidable challenges for underprivileged and marginalised communities. Despite strides made since the post-apartheid era, high-quality music education remains an elusive pursuit for many aspiring musicians. This study used a qualitative approach to explore and dissect the multifaceted challenges that hinder access to quality education within South African music schools. Adopting a descriptive phenomenological research design, this investigation involved ten music lecturers from diverse universities using the snowball sampling procedure. The interviews conducted using Microsoft Team, Zoom, and Google Team served as the primary means of data collection. Colaizzi’s phenomenological data analysis technique was applied to distil rich insights from the participants’ narratives, offering an in-depth exploration of their experiences and perceptions. The study unravels four overarching themes, each shedding light on critical aspects of the challenges faced by underprivileged and marginalised communities in South African music education. These themes include the music lecturers’ perspectives on inclusivity and diversity in the music education curriculum, the challenges encountered by students from underprivileged backgrounds, the socio-economic impact on student engagement, and the role of cultural representation in creating an enriching educational environment. The study concludes that South African music education faces challenges related to inclusivity, diversity, socio-economic disparities, and cultural representation, which hinder access for underprivileged communities. Recommendations include revising the curriculum to incorporate diverse cultural perspectives, implementing support systems for underprivileged students, addressing socio-economic barriers through policies and initiatives, and enhancing cultural representation in music education.